The Relationship Basic Knowledge of The Art of Design And Student Creativity With Make Up Character Competence - Vita Pujawanti Dhana (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This research aims to determine and analyze the relationship between Basic Knowledge of Design Art and Creativity with Character Make-up Competence of Student. This research is classified as quantitative research with a correlational approach. The sample in this research amounted to 26 people with a saturated sample technique. The data is taken through a questionnaire arranged with a Likert scale that has been tested for validity and reliability. First result, testing the first hypothesis stated that there was a positive relationship between basic knowledge of the art of design and the competence of character makeup. This is indicated by a simple linear regression equation = 48.66 + 0.388 which has been tested for significance at = 0.05. Furthermore, through the results of a simple correlation test, the correlation ry1 is 0.604 and the coefficient of determination r2y1 is 0.364. This means that 36.4% of the character's makeup competence is determined by the basic knowledge of the art of design. Second, the results of testing the second hypothesis state that there is a positive relationship between creativity and character makeup competence. This is indicated by a simple linear regression equation = -9.75 + 0.984 X2 which has been tested for its significance at = 0.05. Furthermore, through the results of a simple correlation test, it was obtained that the ry2 correlation was 0.728 and the coefficient of determination r2y2 was 0.575. This means that 57.5% of the character's makeup competence is determined by creativity. Third, the results of testing the third hypothesis state that there is a positive relationship between basic knowledge of design art and creativity together with character makeup competence.